A Comparative Study Of Reading Authentic And Non-Authentic Text - Zainal, Zaidah; Baskeran, Prema (2010)
The present study was designed to investigate the students’ reading performance when they read authentic and non-authentic text. For comparative purpose, students who obtained Band 4 in MUET had been identified and selected. These students were grouped into two groups. Each group consists of fifteen students. One group of students was given the authentic text to read and another group of students was given the non-authentic text to read. Later, they were instructed to answer the comprehension questions based on the reading text. Interviews were carried out to further explore the subjects’ responses on the two reading text types. The result of the study showed that non-authentic text was able to facilitate subjects’ comprehension process better. The results were discussed further. Suggestions for future research were also made.